Effectiveness of Pianica Musical Instruments as a Medium to Increase Nationalism Through the Song "Ibu Kita Kartini" - Mazida, Risma Hanim; Solikha, Fatimatus; Wijayanto, Wasis (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This research is based on the limitations of studies on the use of piano musical instruments and the national anthem "Ibu Kita Kartini" as an effective learning medium to increase student nationalism. The main goal is to analyze how the piano instrument can be used as a means of learning to strengthen the character of nationalism through the song. Research Methods: The method used is a qualitative descriptive approach with a case study, involving 26 grade IV students at SD Negeri Jambean 03. Data was collected through questionnaires, interviews, and observations, and then analyzed using the Miles and Huberman techniques. Finding/Results: The results showed a significant increase in the level of nationalism from 46% to 88%, which was measured through questionnaires and observations. These findings support the theory that the national anthem can be used as a medium of character education at the elementary level. Conclusion: The main conclusion emphasizes the role of piano instruments as an effective medium in increasing student nationalism through the song "Ibu Kita Kartini". The implications of this study include the enrichment of literature on the effectiveness of music media in fostering the character of nationalism as well as practical recommendations for education to integrate music media, especially pianika, in the national song curriculum. This research also opens up opportunities for further studies related to the influence of traditional musical instruments or digital technology in increasing nationalism at various levels of education and cultural backgrounds.